O adoecimento mental dos trabalhadores da agroindústria avícola e a relação com a organização do trabalho - Machado, Leila de Fátima (2016)
The poultry agribusiness in Brazil has been responsible for high production rates in the economy as well as for increasing rates concerning physical and mental illness in workers. The ongoing denial regarding the relation between work and illness has caused several problems to workers lives. Thus, this research aimed at investigating the relations between work and mental illness of workers at the poultry agribusiness. It was a fieldwork, with a qualitative approach, developed at the mental health service of the Unified Health System (SUS) in a Western Paraná city, whose theoretical framework was Worker s Occupational Health. The study sample consisted of 14 workers from the poultry agribusiness, who were treated at an outpatient clinic and two psychosocial care centers. Data collection was carried out by semi-structured interviews and documentary research, with instruments developed for such purpose. The results indicated that the seven men and seven women, aged between 22 and 62 years old, worked on four different freezing poultry storage enterprises, an aviary and a poultry farm, who reported the need and desire to work at poultry agribusiness. During their daily work and life experience, this dream began to be described as a nightmare. According to the physical, mental exploitation, ethical violation, moral and sexual harassment, depreciation, disrespect and humiliation, workers were affected by feelings such as hardship and illness. It was found out that the experiences in the poultry agribusiness were crucial for diseases development. The work organization was done by dividing tasks and subjects in their interpersonal relationships, the leading of loss of mental health process. The acceptance of this relationship is important to ensure rights for those people who become ill in and because of their jobs. So, some discussion concerning this issue should be encouraged with those healthcare professionals and the workers themselves.